Pengaruh Lokasi terhadap Penjualan Ayam Geprek Pakde Kota Palembang - Raul Fernanda; Iceu Sri Gustiana (STIKes Ibnu Sina Ajibarang, 2024)
Ayam geprek is a popular dish, especially in big cities like Palembang. Currently, many ayam geprek businesses are found, one of which is Ayam Geprek Pakde which has a strategic location surrounded by student boarding houses and several higher education institutions. This study aims to analyze the effect of location on sales of Ayam Geprek Pakde in Palembang City. The culinary business, especially ayam geprek, has great potential in the Indonesian market, especially in areas with high populations such as Palembang. In this context, the choice of business location is an important factor that influences accessibility, visibility, and consumer purchasing decisions. This study uses a descriptive qualitative method to understand consumer perspectives on ease of access, price, and service quality. The results show that strategic locations near boarding houses and universities increase consumer interest, especially students. Accessibility factors, competitive prices, menu variations, and service interactions play a role in influencing purchasing decisions. This study provides an understanding for small and medium enterprises (SMEs) about the importance of location selection as a strategy to increase sales and competitiveness in the culinary industry.